Desarrollo sostenible, medio ambiente y economía en el sector forestal - Dávalos Sotelo, Raymundo; Morosini Cordero, Francisco (Instituto de Ecología, A.C., 2016)
The relationships between economy and environment are analized within the context of sustainable development in the forest sector of México. The central argument is that the premises of both are not necessarily in opposition and that a harmonious development can be achieved, provided that a series of principles are upheld, and in particular, the opinion of all of the society is taken into consideration in the governmental plans. From an ecological point of view, some points in relation with the effects of the industrial production on the global warming are discussed and some ways of mitigating it are mentioned. The challenges that the forest sector faces in México are detailed, along with the impact of the forest industry in the national development. The propositions of a State Forest Development Plan are mentioned, arguing that this sort of plan could be a model for other States. As a conclusion, a positive outlook for the forest industry is foreseen, on the condition that the principles of sustainable development are put into practice with the support of the society as a whole.